Implementation of PBL-based Audiovisual Media to improve Students' Critical Thinking Ability - Ratu Betta Rudibyani; Emmawaty Sofya; Tasfiri Efkar (Jurnal Pendidikan dan Pembelajaran Kimia, 2021)
Abstract Implementasi Media Audiovisual berbasis PBL untuk Meningkatkan Kemampuan Berfikir Kritis Siswa: This implementation research is to find out the audiovisual media based on Problem Based Learning (PBL) in improving students' critical thinking skills. The method used was a quasi-experimental pretest-posttest control group design. The research population was all students of class XI MIPA, one of the senior high schools in Bandar Lampung. The sample was obtained by purposive sampling technique, namely class A as the experimental class (learning using PBL-based audiovisual media) and class B as the control class (learning using conventional media). The application of PBL-based audiovisual media is measured by the difference in the average value of n-Gain which is significant on students' critical thinking skills, both in the experimental class and the control class. The results of the calculation of the difference test obtained that the average n-Gain value of students' critical thinking abilities in the experimental class was greater than in the control class. The resulting effect size calculation can be interpreted as learning with PBL-based audiovisual media has an effect on increasing students' critical thinking skills on redox material, by 81%. The conclusion is that the application of PBL-based audiovisual media has an effect and is effective on increasing students' critical thinking skills.Keywords: PBL-based audiovisual media, critical thinking skills.DOI: 10.23960/jppk.v10.i3.2021.14